Integrated biomaterials in tissue engineering - Ramalingam, Murugan (Biomaterials science, engineering, and technology., 2012)
This book acts as a self-contained resource for understanding the current technological advancement of biomaterials towards tissue engineering applications. It covers impact of biomaterials at different length scales such as macro/micro/nano/ level and offers extensive discussion on cell-biomaterial interactions with illustrative examples.